Impact of postoperative dairy consumption on oral wound healing: critical analysis from a prospective, randomized and controlled trial - Tobias Otto; Jan Alfred Dittmann; Jacob Stake; Dirk Szulczewski-Stake; Lukas Schipper; Kai Wermker (Head & Face Medicine)
Abstract Introduction In the German-speaking community of surgeons addressing the oral cavity, there has long been a prevailing opinion that dairy products could be harmful to oral wound healing, but is this true? This study sheds light on this issue based on clinical data of wound healing impairment rates. Methods A patient questionnaire, clinical examination prior to surgery of the oral cavity and a postoperative examination at suture removal were used to assess whether altered wound healing impairment rates occurred because of dairy product consumption. This was done in the setting of a prospective, randomized, controlled, single-blinded, bicenter study in outpatient and inpatient settings. Results Among the 257 patients participating 228 were included in the study, 227 had complete data sets and were used for our statistical analysis. The cohort was randomly divided into 105 dairy product consumers (intervention group) and 123 without dairy products (control group). In total, 45 wound healing impairments out of 227 patients (19.82%) were noted, including 20 (19.05%) in the group of dairy product consumers (intervention group) and 25 (20.33%) in the control group. The logistic regression model was unable to show a statistically significant association between dairy product consumption and wound healing impairment. (p = 0.26), (OR = 0.65). Summary The study found no statistically significant associations that dairy product consumption has either a negative or positive effect on wound healing. (p = 0.26), (OR = 0.65).